2003
DOI: 10.2113/gsecongeo.98.5.1003
|View full text |Cite
|
Sign up to set email alerts
|

Utility of High-Altitude Infrared Spectral Data in Mineral Exploration: Application to Northern Patagonia Mountains, Arizona

Abstract: Synoptic views of hydrothermal alteration assemblages are of considerable utility in regional-scale minerals exploration. Recent advances in data acquisition and analysis technologies have greatly enhanced the usefulness of remotely sensed imaging spectroscopy for reliable alteration mineral assemblage mapping. Using NASA's Airborne Visible Infrared Imaging Spectrometer (AVIRIS) sensor, this study mapped large areas of advanced argillic and phyllic-argillic alteration assemblages in the southeastern Santa Rita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The potassic, phyllic, argillic, and propylitic alteration zones of porphyry copper deposits contain alteration minerals with distinct spectral absorption features (Thompson et al, 1999) that provided they crop out on the surface, can be detected and mapped using multispectral and hyperspectral remote sensing imagery (e.g. Spatz, 1996;Tangestani and Moore, 2002;Berger et al, 2003;Mars and Rowan, 2006;Riley et al, 2009;Pour and Hashim, 2012;among others). Berger et al (2003) used AVIRIS hyperspectral data to map mineral alteration associated with two concealed porphyry copper deposits (Red Mountain and Sunnyside deposits) in the northern Patagonia Mountains of Arizona.…”
Section: Porphyry Copper and Molybdenum Depositsmentioning
confidence: 99%
“…The potassic, phyllic, argillic, and propylitic alteration zones of porphyry copper deposits contain alteration minerals with distinct spectral absorption features (Thompson et al, 1999) that provided they crop out on the surface, can be detected and mapped using multispectral and hyperspectral remote sensing imagery (e.g. Spatz, 1996;Tangestani and Moore, 2002;Berger et al, 2003;Mars and Rowan, 2006;Riley et al, 2009;Pour and Hashim, 2012;among others). Berger et al (2003) used AVIRIS hyperspectral data to map mineral alteration associated with two concealed porphyry copper deposits (Red Mountain and Sunnyside deposits) in the northern Patagonia Mountains of Arizona.…”
Section: Porphyry Copper and Molybdenum Depositsmentioning
confidence: 99%
“…In basaltic hydrothermal alteration systems, alunite is often a minor phase (Swayze et al 2002;Guinness et al 2007;Hynek et al 2013;Marcucci et al 2013). However, large-scale alteration to alunite and kaolinite assemblages mappable by VSWIR imaging spectroscopy is also occasionally observed, driven in part by the duration of magmatic activity at a particular locale (e.g., Berger et al 2003;Swayze et al 2014) Furthermore, the crystallinity of protolith materials can strongly influence weathering products. Weathering experiments by Tosca et al (2004) showed formation of Alsulfates from basaltic glass but not crystalline basalt of identical chemical composition.…”
Section: Environment Of Alunite Formation In Cross Cratermentioning
confidence: 99%
“…Large areas of disseminated pyrite and high-level, advanced argillic hydrothermal mineral assemblages in the northern part of the range are centered on the porphyry Cu-Mo systems at Red Mountain and Sunnyside, and along the Three R shear zone (Corn, 1975;Graybeal, 1996;Berger et al, 2003). In the southern part of the range relatively deep and early potassic alteration assemblages (e.g., Four Metals, Santo Nino, and Line Boy mines; Fig.…”
Section: Geology and Metal Deposits Of The Patagonia Mountainsmentioning
confidence: 99%
“…Alunite is widespread in the northern Patagonia Mountains (Kistner, 1984;Cook, 1994;Berger et al, 2003). It occurs in both hypogene and supergene forms in pervasively altered granitic, volcanic, and sedimentary rocks on Red Mountain, in a 6.5-km-long zone from Three R Canyon to Thunder Mountain (Three R shear zone), and in vein and breccia deposits at the Three R, Sunnyside, and Volcano mines (Fig.…”
Section: Interpretation Of Radioisotopic Ages Of Igneous Minerals In mentioning
confidence: 99%